Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $f(a,x)=\sqrt{a(a-1)+x}$, $f^{(n)}(a,x)$ denotes the $n^{th}$ iteration of $x$, where \begin{align}f^{(1)}(a,x)=f(a,x),f^{(n)}(a,x)=f^{(n-1)}(a,f(a,x))\end{align} Find \begin{align}\lim_{n\to\infty}(2a)^{\frac{n}{2}}\sqrt{a-f^{(n)}(a,0)}\end{align}

This is a problem from a discussion in a forum, someone say that when $a=2$, the limit is equal to $\pi$, but I can't find the pattern behind this structure, Thanks for your attention.

PS: Expanding it shows \begin{align}\lim_{n\to\infty}(2a)^{\frac{n}{2}}\sqrt{a-\sqrt{a(a-1)+\sqrt{a(a-1)+\cdots}}}\end{align} where there are $n$ square root sign behind the minus sign, it is a $\infty \cdot 0$ problem.

share|improve this question
    
Why not discuss it in that forum (secret from us?) instead of here? –  GEdgar Oct 23 '12 at 16:41
    
@GEdgar : Because none of us has found a way to find the limit –  Golbez Oct 23 '12 at 17:17
1  
But I still think it would be better to include the link of that forum. –  GEdgar Oct 23 '12 at 17:28

1 Answer 1

up vote 2 down vote accepted

Steps for solution ... With $a=2$ write $f(2,x) = f(x)$. For the appropriate values of $\theta$ ...

$$\begin{align} &2\cos\theta = \sqrt{2+2\cos(2\theta)} \\ &f^{(n)}(2\cos\theta) = 2\cos\frac{\theta}{2^n} \\ &f^{(n)}(0) = 2\cos\frac{\pi}{2^{n+1}} \\ &\sqrt{2-2\cos\theta} = 2 \sin \frac{\theta}{2} \\ &\sqrt{2-f^{(n)}(0)} = 2\sin\frac{\pi}{2^{n+2}} \\ &\lim_{n\to\infty} 2^n\cdot 2\sin\frac{\pi}{2^{n+1}} = \frac{\pi}{2} \end{align}$$

share|improve this answer
    
When $a$ is arbitary, is it possible to calculate the answer? –  Golbez Oct 24 '12 at 13:29
    
The only complex numbers $a$ for which solution can be done by this method are $a=-1,0,1,2$. Function $f$ is inverse to $z^2+c$ where $c=-a(a-1)$. Iteration of $z^2+c$ in closed form is known only when $c=0$ or $c=-2$. And $-a(a-1)=0$ yields $a=0$ or $a=1$; and $-a(a-1)=-2$ yields $a=-1$ or $a=2$. –  GEdgar Oct 24 '12 at 16:03

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.